The Influence of Supervisor Support and Work-Life Balance on Employees' Personal Lives at PT. Bank Tabungan Negara (BTN) Makassar Sharia Branch Office - Hidayah, Nurul; Handayani, Nurinaya; Akib, Muhammad (Dinasti Publisher, 2025)
This study aims to analyze the effect of supervisor support and work balance on employees' personal lives at PT Bank Tabungan Negara (BTN) Makassar Syariah Branch Office. The research method used is quantitative with a descriptive approach. The population in this study were all employees of PT Bank BTN Syariah Makassar, with saturated sampling technique involving the entire population of 51 people. Data were collected through questionnaires distributed to respondents and analyzed using statistical tests. The results showed that there is a positive and significant relationship between supervisor support and employees' personal lives, which means that the higher the support provided by the supervisor, the better the employees' personal lives. In addition, work balance also has a significant effect on employees' personal lives, indicating that a balance between work and personal life can improve employees' overall well-being. Thus, company management is advised to increase support to employees and create policies that support work balance in order to improve the quality of personal life and overall employee performance.